Polityka gospodarcza i handlowa wybranych krajów Azji Południowo-Wschodniej i Wschodniej - Domiter, Małgorzata (Economic and Trade Policies of Selected South-East and EAST Asian States, 2008)
The second half of the 1960s witnessed the appearance of a group of states which due to their soaring economic dynamism were named New Industrial Countries. Significant development of local capital and export were the two features common for all above-mentioned states. The role of each country in the functioning of those economies was however diverse. The biggest impact could be noted in South Korea, subsequently in Singapore while the least significant input from the country authorities was present in Taiwan. Colonial administration of Hong Kong implemented free market economy model. Korea and Taiwan, ruled by military juntas, were burdened with army expenditures. For this reason all implemented reforms were conducive for thrifty economy and accumulation increase as well as investments directed at the growth of those branches of industry that are foreign markets oriented. Korea being strongly dependent on the United States received American aid in realizing its export policy. Furthermore, Korea actively supported development of industrial-trade societies known as chaebols (similar to Japanese keiretsu). Both Taiwan and Korea having gained significant export surplus and having strengthened their position in the international market, started to gradually realize the strategy of liberalizing import of goods and foreign capital inflow. The experience of those Asian countries that achieved success in development shows relation between growth dynamics of production and export. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 60-70